Constructivism Based Quizizz in Improving Social Studies Learning Activities and Outcomes - Ulfa, Maria; Aliyyah, Rusi Rusmiati (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to analyze the increase in student learning activities and outcomes through the use of the constructivism-based Quizizz application in social studies subjects on Local Wisdom material at SMPN 7 Bima City. The research used a qualitative approach with descriptive methods. Data collection techniques include interviews, observation, and documentation. The research subjects consisted of 25 students in class IX-A. Before the use of Quizizz, the average student pretest score was 52, and increased to 80 on the posttest after learning using Quizizz, showing a significant increase in learning outcomes. In addition, student learning activities also increased, shown through indicators of learning independence, motivation and enthusiasm, cooperation between students, and active participation in taking quizzes. The interactive and gamification features in Quizizz create an interesting and competitive learning atmosphere, encouraging students' active involvement and building their understanding independently. Key constraints such as limited internet access and devices were overcome through training, use of computer labs, and infrastructure improvements. Overall, Quizizz proved to be an effective learning medium in supporting technology-based learning.